TEACHING STRATEGIES USED BY THE LECTURERS AND STUDENT’S RESPONSE IN ENGLISH SPEAKING CLASS - Abdul Shamad Rusani; Andi Tenri Ampa; Muh. Arief Muhsin (Universitas Muhammadiyah Makassar, 2019)
This research aimed to find out teaching strategies used by the lecturers and the Students’ Response to the teaching strategies used by the lecturers in English Speaking Class. This research used a quantitative method. The population of this research was the third-semester students while the sample was 60 students from that population that was taken selectively. The instruments of this research were observation and questionnaire. The first lecturer used telling the story and oral interview while the second lecturer used to role-play and oral interview. Students’ response in the first class for telling story strategy strongly agreed 22.50 %, agree 50.42 %, neutral 24.58 %, disagree 2.08 %, strongly disagree 0.42 %. Therefore, the score range was 3.93. While for oral interview strategy were strongly agree 24.29 %, agree 47.62 %, neutral 26.19 %, disagree 1.90 %, strongly disagree 0 %. Therefore, the score range was 3.94. Students’ response in the second class for role-play were strongly agree 9.58 %, agree 45.83 %, neutral 24.17 %, disagree 14.17 %, strongly disagree 6.25 %. Therefore, the score range was 3.38. While for oral interview strategy were strongly agree 12.38 %, agree 38.57 %, neutral 33.81 %, disagree 8.10 %, strongly disagree 7.14 %. Therefore, the score range was 3.41. The result showed feedback on in the first class, it has been proven that more attractive lecturers to students than the “storytelling” strategy on the first-class use the “oral interview” strategy. Whereas in the second class, it has been proven that lecturers use the “oral interview” strategy is more attractive to students than the